Children's home and school neighbourhood exposure to alcohol marketing: Using wearable camera and GPS data to directly examine the link between retailer availability and visual exposure to marketing. (November 2018) - Chambers, T.; Pearson, A.L.; Kawachi, I.; Stanley, J.; Smith, M.; Barr, M.; Mhurchu, C. Ni; Signal, L.
Abstract: Background and aim: Neighbourhood alcohol availability has been associated with alcohol consumption by children, despite children rarely acquiring alcohol from retailers. This study explores one potential reason for this finding, by evaluating the relationships between neighbourhood alcohol availability and children's actual exposure to alcohol marketing. Method: Wearable cameras and GPS devices were worn by 167 children (aged 11–13 y) over a four-day period. Image and GPS data were linked and compared to known alcohol availability data. Results: Off-licence retailer availability and ethnicity were positively associated with children's exposure to marketing in both residential and school neighbourhoods. Conclusion: Neighbourhood off-licence alcohol retailers are associated with increased childhood exposure to alcohol marketing. Highlights: Examines the relationship between alcohol availability and exposure to alcohol marketing. Uses combined image and GPS data to provide objective estimates of children's real-time exposure. Off-licence retailers were positively associated with children's exposure to alcohol marketing. Māori children experienced high rates of neighbourhood exposure to alcohol marketing.